El discurso práctico y su relación con el discurso jurídico - Cuchumbé Holguín, Nelson Jair (2011)
This article discusses the interpretation of Jürgen Habermas of the logic of practical discourse. This interpretation allows us to base communicative actions on ethical assumptions. This alternative has been collected and included by Robert Alexy in his Theory of Legal Argument to show how legal discourse is a special case of practical discourse, since in legal spheres the administrators of justice use normative wording which should be based on and justified by correct criteria. This intention permits the understanding that legal discourse is a part of practical discourse.